LONG-TERM SAFETY OF ALEMTUZUMAB IN RELAPSING-REMITTING MULTIPLE SCLEROSIS: PREGNANCY AND INFECTION DATA FROM A COHORT OF PATIENTS ON OPEN LABEL STUDIES IN CAMBRIDGE. Issue 11 (14th October 2015) - McCarthy, Claire; Tuohy, Orla; Azzopardi, Laura; Kousin-Ezewu, Onajite; Jones, Joanne; Compston, Alastair; Coles, Alasdair
Abstract : Background: Alemtuzumab is recently licensed for use in active relapsing-remitting multiple sclerosis (RRMS) in Europe and the USA. This observational cohort study investigated the long term safety of alemtuzumab in RRMS. Methods: Clinical data was collected from a cohort of 87 patients who participated in open label studies of alemtuzumab in Cambridge, UK from 1999 to 2012. Pregnancy outcomes and the occurrence of moderate to severe infections were recorded. Results: Over a median 7-year follow-up (range 33–144 months), no serious infections occurred that required hospitalisation. There were 11 cases of varicella zoster virus reactivation and one case of primary varicella zoster virus infection. In this cohort 15 babies were born to 12 women treated with alemtuzumab. The median interval from their most recent alemtuzumab treatment to birth was 26 months (range 13–86 months). All of the babies were healthy and delivered without complications. One woman had experienced a miscarriage at 8 weeks gestation but went on to have two successful pregnancies. Conclusions: During prolonged follow-up of this cohort of patients treated with alemtuzumab no serious infections occurred. No increased risk of miscarriage or foetal abnormality was seen in the small number of pregnancies studied.